The post-Marcos Supreme Court rulings in illegal dismissal cases - Agbayani, Kim Patrick G.
This study analyzes non-unanimous decision of the post-Marcos Philippine Supreme Court labor disputes, particularly those involving claims of illegal dismissal. It aims to explore how inter-institutional interactions bear on Supreme Court ruling in such cases. The study suggests that the decisions of the highest court in the land are not only grounded on just the law and the circumstances of a case but also on extra-legal factors. The study also examines whether Supreme Court decisions in non-unanimous illegal dismissal cases tend to favor employees over employers --Author's abstract.